Inoculation of Lactobacillus buchneri alone or with Bacillus subtilis and total losses, aerobic stability, and microbiological quality of sunflower silage. Issue 1 (1st January 2017) - Gandra, Jefferson Rodrigues; Oliveira, Euclides Reuter; Gandra, Erika Rosendo de Sena; Takiya, Caio Seiti; Goes, Rafael Henrique Tonissi Buschineli de; Oliveira, Kelly Mari Pires; Silveira, Karina Andrade; Araki, Hayne Mayume Cariolano; Orbach, Natyaro Duan; Vasquez, Dalila Nara
ABSTRACT: The purpose of this study was to evaluate the effects of inoculation of Lactobacillus buchneri ( L. buchneri ) alone or with Bacillus subtilis ( B. subtilis ) on gas and effluent losses, chemical composition, in vitro digestibility of nutrients, aerobic stability, and microbiological quality of sunflower silage. A randomized experimental design was used, which contained 3 treatments, each one included 15 mini-silos. Mini-silos were distributed to the following treatments: (1) Control (CON), without inoculants; (2) L. buchneri alone (LB), inoculation at 2.6 × 10 10  cfu/g; and (3) L. buchneri with B. subtilis (LB + BS), inoculation at 2.6 × 10 10  cfu/g and 1 × 10 9  cfu/g with L. buchneri and B. subtilis, respectively. Treatments were applied at 2 g/t of fresh forage ensiled. Silages with microbial inoculants had lower DM content, and higher in vitro digestibility of DM and neutral detergent fibre than CON. Inoculants decreased the number of aerobic bacteria, mould, and yeast, and increased the counts of lactic acid bacteria in sunflower silage. L. buchneri exhibited positive effects on aerobic stability, in vitro digestibility of nutrients and decreased the counts of mould and yeast, but did not show a synergistic effect with B. subtilis on sunflower silage.